Penanaman Nilai Karakter Peserta Didik Melalui Program Pengembangan Diri - Rifdah Hasan Parinduri; Riskang Aj Pahruzi; Sutrisno Sutrisno (Continuous Education: Journal of Science and Research, 2022)
The purpose of this study was to determine the effect of self-development programs for students implemented at Madrasah Tsanawiyah Muallimin Univa Medan, as well as leadership policies in instilling character values. In addition, it also aims to find out what supports and hinders the cultivation of character values ??through self-development programs at Madrasah Tsanawiyah Muallimin Univa Medan. This research is included in the category of qualitative research using a phenomenological perspective. The findings of this study show how Madrasah Tsanawiyah Muallimin Univa Medan integrates the development of character values ??into learning by focusing on three different areas: teaching, modeling, and assessment. Madrasah Tsanawiyah Muallimin Univa Medan implements the policy of the madrasah head to teach character values ??through working meetings with the teacher council in the context of instilling character values ??in students. In addition, this study examines the facilitating and inhibiting elements that influence how students at Madrasah Tsanawiyah Muallimin Univa Medan build character.